ANALISIS POTENSI KEBANGKRUTAN PERUSAHAAN DENGAN MENGGUNAKAN MODEL SPRINGATE (S-SCORE) (Studi Pada Perusahaan Pertambangan Batubara yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Kristi, Utami Wahyuning (Jurnal Ilmiah Mahasiswa FEB, 2017)
The 2008 global economic crisis has caused a decline in coal mining business, making the international market oversupplied with the commodity and pushing the price low. Therefore, many companies are faced with the risk of bankruptcy.The purpose of this research is to identify the potential of bankruptcy in coal mining companies in Indonesia using Springate S-score model. This descriptive study describes the current state of companies using quantitative data. The population of this study is 23 coal mining companies listed in the Indonesia Stock Exchange in the period of 2014-2016. The sample of this study were selected through purposive sampling method, resulting in 19 mining companies. The variables used in Springate S-score model are X1 = Net Working Capital to Total Assets, X2 = EBIT to Total Assets, X3 = EBT to Current Liabilities, and X4 = Sales to Total Assets.The results show that there were six companies that did not have bankruptcy potential for three consecutive years; they were PT Indo Tambangraya Megah Tbk, PT Resource Alam Indonesia Tbk, PT Toba Bara Sejahtera Tbk, PT Mitrabara Tbk, PT Samindo Resources Tbk, and PT Bukit Asam Tbk. There were six companies that experienced S-score value fluctuations and had the potential to go bankrupt in 2014 and 2015. However, these companies were able to improve their financial performance, so they did not have the potential to go bankrupt in 2016. Furthermore, there were seven companies that had bankruptcy potential for three consecutive years; they were PT Atlas Resources Tbk, PT Bumi Resources Tbk, PT Darma Henwa Tbk, PT Petrosea Tbk, PT Barajaya International Tbk, PT Golden Eagle Energy Tbk, and PT Perdana Karya Perkasa Tbk. Most of the companies with bankruptcy potential had low liquidity and profitability level, so their financial and managerial performance were decreasing.Keywords: bankruptcy, Springate S-Score model, Net Working Capital to Total Asset, EBIT to Total Asset, EBT to Current Liabilities, Sales to Total Asset